2018
DOI: 10.1371/journal.pone.0191724
|View full text |Cite
|
Sign up to set email alerts
|

Association between socioeconomic status and cerebral palsy

Abstract: BackgroundThe present study investigated the annual prevalence of cerebral palsy (CP) among children aged <7 years in Taiwan and the association between socioeconomic status and CP prevalence.MethodsData from the Taiwan National Health Insurance Research Database for the 2002−2008 period were used in this population-based study. Severe and total CP were defined according to catastrophic illness certificate and medical claim records, respectively. The annual CP prevalence was calculated as the number of childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 27 publications
2
23
2
1
Order By: Relevance
“…Our findings concur with international research that has demonstrated that low neighbourhood SES is associated with increased risk of severe intellectual impairment and greater motor impairment . Our study is the first to show a relationship between low neighbourhood SES and the presence of severe comorbidities other than intellectual impairment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings concur with international research that has demonstrated that low neighbourhood SES is associated with increased risk of severe intellectual impairment and greater motor impairment . Our study is the first to show a relationship between low neighbourhood SES and the presence of severe comorbidities other than intellectual impairment.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings concur with international research that has demonstrated that low neighbourhood SES is associated with increased risk of severe intellectual impairment 14 and greater motor impairment. [15][16][17] Our study is the first to show a relationship between low neighbourhood SES and the presence of severe comorbidities other than intellectual impairment. In Canada, the relationship between low neighbourhood SES and reduced mobility in 5-year-old children with CP was only seen in those who were born preterm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings may very well correlate with the fact that the timing of treatment of UDT in general can be influenced by those socio-economic fac- tors. Certainly, it would be a tragedy if those who are at a higher risk for CP share the same risk factors for late or insufficient management of UDT [Kokorowski et al, 2010;Springer et al, 2012;Forthun et al, 2018;Tseng et al, 2018]. In a recent systematic review the lifetime financial burden of patients with CP have been discussed.…”
Section: Ethical Issuesmentioning
confidence: 99%
“…Most common residential location of the CP patients was the rural areas similar to the literature. 17 Most of the male CP patients were living in the city where the females were living in villages. Contrast to the previous reports 18 the education level of the CP patients' parents in our study was very low.…”
Section: Discussionmentioning
confidence: 99%